Uso(s) do livro didático por professores de matemática dos anos finais do ensino fundamental de escolas da rede estadual de Aracaju/SE - Jesus, Franckline Juliana Alves de (2017)
In this text are presented results of a research whose objective was to identify "if" and "how" mathematics teachers of the final years of Elementary School of public school of Aracaju/Se make use of textbook. For this, the collections listed in the Plano Nacional do Livro Didático – PNLD 2014 was taken as a starting point, more adopted by schools. Are they: “Matemática: Teoria e Contexto”, “Vontade de Saber Matemática”, “Matemática – Bianchini” and “Projeto Teláris”. From this choice, twety-three teachers were selected to participate answering the questionnaire and after that total thirteen were interviewed. The theoretical contribution came from the appropriation of the understanding adopted by Moreira (2013) to define textbook; Dante (2005) for the typification of mathematical problem and Fiorentini and Lorenzato (2006) about the Mathematics Education, and results of the researches of Silva Junior (2005), Oliveira (2007) Rosas (2008) and Vieira (2013) to characterize use (s) of the adopted of the textbook. From the data collected, through the two instruments, the following uses have been identified: the first is the preparation to teach, this is, the use of textbook to prepare class – at this moment they often resort to other materials as a way to provide more information to their students. The second is the action to teaching and learn, this use realized with the students to read texts related to daily life and the history of mathematics, concepts, examples and statements of problems; to solve the problems proposed in the textbook with (or not) the use of technological resources and instruments of measures.